Serum 8-isoprostane increased in pre-eclampsia - Pramono, Besari Adi; Kristanto, Herman (Universa Medicina, 2012)
Background The main causes of maternal mortality in Indonesia are pre-eclampsia, hemorrhage, and infection. Oxidative stress has a primary role in pre-eclampsia and one of its parameters is 8-isoprostane serum level. The objective of this study is to measure 8-isoprostane and to analyze the relationship between 8-isoprostane level and birth weight in pre-eclampsia.Methods A cross-sectional study involving 23 pre-eclampsia and 29 normotensive pregnant women with normal or cesarean delivery at Dr. Kariadi Hospital Semarang from January to May 2011. Collected maternal blood samples were assessed for 8-Isoprostane levels by means of a specific ELISA kit. Neonatal birth weight was measured immediately after delivery by means of calibrated baby scales. Differences in 8-isoprostane levels between pre-eclampsia and normotensive women were assessed using independent t-test for normal distributed data, and the Mann-Whitney test for non-normally distributed data. ResultsMean 8-isoprostane level was significantly higher in women with pre-eclampsia than in normotensive women (62.52 Â± 12.19 pg/mL vs 28.64 Â± 8.81 pg/mL) (p<0.05). Low birth weight was twice as frequent in pre-eclampsia than in normotensives. There was no correlation between 8-isoprostane serum level and neonatal birth weight in pre-eclampsia.Conclusion The level of 8-isoprostane was higher in pre-eclampsia than in normotensives. It is recommended to conduct further studies to determine whether 8-isoprostane may be used as a predictive marker of pre-eclampsia.